Comparing the effects of intercostal and subcostal flank incision on post-operative pain and incisional hernia or bulge in patients undergoing open kidney surgery: A randomized clinical trial - Alireza Abdi; Behzad Imani; Seyed Habibollah Mousavibahar; Salman Khazaei; Shima Bahrami Jalal (International Journal of Abdominal Wall and Hernia Surgery)
BACKGROUND: Flank incision, a common approach in kidney surgery, has several types. This study was carried out to examine the effect of using subcostal and intercostal flank incisions on post-operative pain, incisional hernia or bulging, and incision time and wound closure time in patients undergoing open kidney surgery. MATERIALS AND METHODS: This randomized clinical trial was conducted Iran (2023–2024). Sixty-four patients were randomly divided into two groups of 32 patients, subcostal and intercostal, based on available sampling technique. The Visual Analog Scale was used to assess post-operative pain. The abdominal wall asymmetry (AWA) technique was used for both hernia and bulge, and clinical examination was done by a urology surgeon for diagnosing AWA. Data analysis was done using SPSS-23. RESULTS: In the subcostal group, a higher incidence of AWA was observed when compared to the intercostal group at 6 months post-operation, and this difference was statistically significant (P = 0.039). However, there was no significant difference between the two groups at 3 months post-operation in this regard (P > 0.05). The mean pain score of patients at 24 and 72 h post-operation was significantly higher in the intercostal group than in the subcostal group (P < 0.05); however, at the first hour and on day 7 post-surgery, no significant difference was found between the two groups in this regard (P > 0.05). In addition, no significant differences existed between the two groups regarding incision time and wound closure time (P > 0.05). CONCLUSION: Intercostal incision, when compared to subcostal incision, was associated with lower probability of development of hernia or bulge, in spite of its higher-level post-operative pain. TRIAL REGISTRATION: This study was registered with the Iranian Clinical Trials Registry under the code IRCT20230208057358N1 on 2023.02.11.